2018
DOI: 10.3390/nu10060729
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium after Kidney Transplantation: A Systematic Review

Abstract: Magnesium (Mg) status has recently drawn close attention in chronic kidney disease and in kidney transplant recipients. This review aims to evaluate the body of evidence linking hypomagnesemia to clinical consequences in these specific populations. After a brief summary of the main mechanisms involved in Mg regulation and of Mg status in end-stage renal disease, the review focuses on the relationship between hypomagnesemia and cardiovascular risk in kidney transplant recipients. A body of evidence in recent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 76 publications
0
22
1
4
Order By: Relevance
“…In kidney transplant recipients, hypomagnesemia has been shown to be associated with various adverse consequences[49]. Low magnesium level has been associated with accelerated decline of allograft function and a higher rate of graft loss in patients with cyclosporine-induced nephropathy[50], consistent with animal studies showing a higher degree of renal tissue fibrosis associated with low magnesium[51] that appears to be partially correctable with magnesium supplementation[51,52].…”
Section: Discussionmentioning
confidence: 84%
“…In kidney transplant recipients, hypomagnesemia has been shown to be associated with various adverse consequences[49]. Low magnesium level has been associated with accelerated decline of allograft function and a higher rate of graft loss in patients with cyclosporine-induced nephropathy[50], consistent with animal studies showing a higher degree of renal tissue fibrosis associated with low magnesium[51] that appears to be partially correctable with magnesium supplementation[51,52].…”
Section: Discussionmentioning
confidence: 84%
“…Differences in kidney function may be a consequence of CNImediated kidney damage and consistent with the previous phase II trial, 7 while lower magnesium levels are likely due to tacrolimus decreasing tubular reabsorption. 6 Magnesium is essential for insulin secretion and insulin actions and thus it is possible that tacrolimus-induced hypomagnesemia could explain our findings, 10 however additional investigation is warranted. In conclusion, our study provides evidence that belatacept is associated with lower rates of diabetes and prediabetes than tacrolimus.…”
Section: To the Editormentioning
confidence: 81%
“…The characteristics of both patient groups, by OGTT status, are shown in Table 1 and indicated that tac-KTRs with NGT, in comparison to bela-KTRs with NGT, had higher HbA1c levels, lower insulin release, higher insulin sensitivity, lower magnesium levels and higher serum creatinine levels (corresponding with lower estimated glomerular filtration rates [eGFRs]; all p ≤0.05). Besides magnesium, other risk factors for PTDM, 6 including age, body mass index and polycystic kidney disease, did not differ between tac-KTRs and bela-KTRs (ancestry is not routinely recorded at our transplant center and could not be reported). Insulin release and insulin sensitivity were regressed on 2-hour glucose (Figure 1).…”
Section: To the Editormentioning
confidence: 96%
“…Hypomagnesemia has been shown to be an independent predictor for the development of post-transplant diabetes in kidney transplant recipients [30].…”
Section: Cardiovascular Manifestationsmentioning
confidence: 99%